Synthesis and characterization of activated carbon derived from Tectona grandis sawdust via green route - Singh J.; Mishra V. (My University, 2025)
High quality activated carbon was successfully produced from Tectona grandis sawdust by chemical activation using potassium chloride and sodium thiosulphate in a ratio of 1:1.5:1. Surface characterization of sawdust and activated carbon showed the presence of several functional groups such as hydroxyl, ketones, phenols, carboxylic acids, aldehydes and aryl halide together with the heterogeneous surface and extensive porous network as depicted by morphological characterization. It was found that the per cent yield by mass of Tectona grandis sawdust was 52% (SD ± 0.41%). The content of fixed carbon (67.3%) and volatile matter (13.7%) in T. grandis sawdust signifies the ease with which it can be ignited and oxidized. The x-ray diffraction analysis of activated carbon prepared from T. grandis sawdust indicated amorphous behavior of activated carbon. In the present work, activated carbon possesses 8.76 pH zero-point charge, 1270 m2/g BET surface area, 0.673 cm3/g total pore volume and 0.42 g/cm3 bulk density. © 2020 American Institute of Chemical Engineers